Hubungan Tingkat Kesejahteraan Spiritual dengan Tingkat Kecemasan Mahasiswa dalam Menghadapi Objective Structured Clinical Examination (OSCE) - Bagus Maulana Akbar; Sherly Limantara; Dona Marisa (Homeostasis, 2020)
Abstract: In students, anxiety affects the educational process. Anxiety in medical students can occur to approach the OSCE. Spiritual well-being is one of the factors that contribute to reducing the individual anxiety level. This study aims to determine the relationship between spiritual well-being level and anxiety level among the medical students in facing OSCE at PSPD FK ULM class of 2017. This study uses an observational analytic with a cross-sectional method. Respondents were selected using a purposive sampling technique. A total of 91 respondents were asked to fill the Hamilton Anxiety Rating Scale (HARS) questionnaire and the Spiritual Well-Being Scale (SWBS) questionnaire. Data analysis using the Chi-square test with 95% confidence interval showed the value of p = 0.003. Based on the Spearman rank correlation test, showed the value of r = -0.373. From this study, it can be concluded that obtained a relationship between the level of spiritual well-being with the level of student anxiety in dealing with OSCE on the PSPD FK ULM class of 2017. Keywords: spiritual well-being, anxiety, OSCE Abstrak: Pada mahasiswa, kecemasan berpengaruh terhadap proses pendidikan. Kecemasan pada mahasiswa kedokteran dapat terjadi menjelang OSCE. Kesejahteraan spiritual merupakan salah satu faktor yang berkontribusi menurunkan tingkat kecemasan individu. Tujuan penelitian ini adalah untuk mengetahui hubungan tingkat kesejahteraan spiritual dengan tingkat kecemasan pada mahasiswa kedokteran PSPD FK ULM angkatan 2017 dalam menghadapi OSCE. Penelitian ini bersifat observasional analitik dengan metode cross sectional. Responden dipilih menggunakan teknik purposive sampling. Sebanyak 91 responden penelitian mengisi kuesioner Hamilton Anxiety Rating Scale (HARS) dan kuesioner Spiritual Well-Being Scale (SWBS). Data dianalisis menggunakan uji Chi-square dengan tingkat kepercayaan 95%. Didapatkan hasil nilai p=0,003. Berdasarkan uji korelasi Spearman rank didapatkan nilai r = -0,373. Kesimpulan penelitian ini adalah terdapat hubungan bermakna antara tingkat kesejahteraan spiritual dengan tingkat kecemasan mahasiswa dalam menghadapi OSCE di PSPD FK ULM angkatan 2017. Kata-kata kunci: kesejahteraan spiritual, kecemasan, OSCE